Palm-vitamin E supplementation on the indices endothelial function of pregnant women at risk of pre-eclampsia - Noor Azliza Wani binti Abdul Aziz (Kuliyyah of Science, International Islamic University Malaysia, 2008)
Prophylactic treatment with antioxidants such as vitamin E is suggested to prevent pre-eclampsia (PE). Since the exact pathophysiology of PE is unknown, poor placentation is believed to play an important role. In recent years, it has been postulated that endothelial dysfunction in PE can be highly attributable to oxidative stress. A randomized, double-blind placebo controlled clinical trial named as REPP STUDY (role of palm-vitamin E in the prevention of pre-eclampsia) involving 299 primigravidae was conducted in Hospital Universiti Kebangsaan Malaysia. Subjects (44) for this study were randomly selected from this pool of subjects; they consisted of 19 subjects of the palm-vitamin E group and 25 subjects of the placebo group. Peripheral blood collected at baseline, weeks 28, 32, 36 of gestation and at delivery were analyzed for PECAM-1 expression by reverse-transcription polymerase chain reaction (RT-PCR). Plasma 6-keto PGF1α and TXB2 levels were determined by enzyme-linked immunosorbance assay (ELISA). Blood of subjects who later developed pregnancy-induced hypertension (PIH) (n=9) and PE (n=6) were compared to those of normal pregnancies. PECAM-1 expression was found to be significantly lower in the palm-vitamin E subjects compared to the placebo subjects at weeks 28, 32 of gestation and at delivery (P<0.05). Subjects in the placebo group who developed PIH and PE showed high expression of PECAM-1 throughout pregnancy. However, increased expression was only observed during admissions in the palm-vitamin E group. The levels were significantly higher when compared to week 32 of gestation (P<0.05). Plasma 6-keto PGF1α/TXB2 ratio was consistently high in the palm-vitamin E group compared to the placebo group in normal pregnancies, but not in the PIH and PE pregnancies. A plasma 6-keto PGF1α/TXB2 ratio lower than 1.6 specifically at week 36 gestation was suggested as a possible index in PIH and PE pregnancies. This study provides evidence of decreased plasma 6-keto PGF1α/TXB2 ratio as an early index of PIH and PE in pregnant women destined to develop the disorder. PECAM-1 expression was found to be an index of endothelial dysfunction during the onset of PIH and PE.